2022
DOI: 10.3390/ijerph19116619
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Mapping of Online Interest in Cannabis and Popular Psychedelics before and during the COVID-19 Pandemic in Poland

Abstract: Background: Psychedelics represent a unique subset of psychoactive substances that can induce an aberrant state of consciousness principally via the neuronal 5-HT2A receptor. There is limited knowledge concerning the interest in these chemicals in Poland and how they changed during the pandemic. Nonetheless, these interests can be surveyed indirectly via the web. Objectives: We aim to conduct a spatial-temporal mapping of online information-seeking behavior concerning cannabis and the most popular psychedelics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Further, divergent perspectives on psychedelics also yielded notably distinct awareness scores, particularly among those with positive versus negative opinions on psychedelics (15, [9.5, 18] vs. 7, [3,13], p < 0.001). In contrast, medical students who perceived sporadic psychedelic use as low-risk consistently achieved higher scores than those who perceived it as high-risk (11.5 [5,17] vs. 7, [2,14], p < 0.001). As anticipated, individuals with psychedelic use experience exhibited notably higher scores than non-users.…”
Section: Knowledge Of Psychedelics Across Other Survey Parametersmentioning
confidence: 84%
See 1 more Smart Citation
“…Further, divergent perspectives on psychedelics also yielded notably distinct awareness scores, particularly among those with positive versus negative opinions on psychedelics (15, [9.5, 18] vs. 7, [3,13], p < 0.001). In contrast, medical students who perceived sporadic psychedelic use as low-risk consistently achieved higher scores than those who perceived it as high-risk (11.5 [5,17] vs. 7, [2,14], p < 0.001). As anticipated, individuals with psychedelic use experience exhibited notably higher scores than non-users.…”
Section: Knowledge Of Psychedelics Across Other Survey Parametersmentioning
confidence: 84%
“…According to the literature, the level of interest in psychedelics is not static and may fluctuate throughout the year [ 4 ]. A study conducted in 2022 revealed intriguing seasonal patterns of interest in psychedelics in Poland, with some fluctuations correlating with school breaks and holidays, while the emergence of the SARS-CoV-2 pandemic introduced additional complexities, causing shifts in temporal and spatial trends due to lockdown measures and changes in individual and societal behaviors, while the latter may relate to social anomie theory [ 5 , 6 ]. Notably, the authors identified that psilocybin and ayahuasca exhibited annual seasonality coinciding with the mushroom harvest season in Poland (September and October) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Internet users who surf the web could have used virtual private networks applications, Internet protocol (IP) masking, or implemented anonymous web browsing via the Tor browsers or DuckDuckGo search engine, among others, to conceal the actual geographic location and identity while browsing the web for critical information concerning psychedelics [ 76 ]. More advanced web users might use the deep web and darknet to seek information concerning DMT and other controlled substances, or even purchase them [ 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%